Book publishing encyclopedia : tips & resources for authors & publishers - Poynter, Dan ([Electronic & Database Pub.], 2006)
Dan Poynter's 'Book Publishing Encyclopedia' is the "Book Publishing answer Book." It has thousands of tips and references in an easy-to use alphabetical encyclopedia. Each fact, figure, resource or reference, in its 222 pages, links to a specific page on a web site for more information. Time is money. Writers, publishers and publicists need access to resources-quickly. Whether they deal in entertainment (fiction) or information (nonfiction), they need information on the book industry. Poynter's Encyclopedia is also made available in softcover, large print and four types of eBook. All are laid